Evaluasi Proses Perda Nomor 3 tahun 2013 tentang Kawasan Tanpa Rokok di Fasilitas Kesehatan (Rumah Sakit dan Puskesmas) Wilayah Kecamatan Tembalang Kota Semarang - Rio Dewandika Putra; Priyatno Harsasto; A Taufiq (Journal of Politic and Government Studies, 2015)
Non-Smoking Area was established by the government in order to provide effective protection for the people toward the dangers of cigarette smoke. Semarang City became one of the cities that apply on Non-Smoking Area through Local Government Regulation No.3 year of 2013, which is responsible for the Non-Smoking Area is a leader or manager of each region. In this case, the cooperation was needed from related parties in order to improve the performance of the apparatu sto the adoption and implementation of Non-Smoking Area both in hospitals and health centers as organizers of helath facilities. This studyusing qualitative research methods. The technique of collecting data through observation, interviews, and documentation. The purpose of this research are to know the evaluation of Local Government Regulation No.3 year of 2013 about Non-Smoking Area in health facilities(hospitals and health centers) of Semarang City and to know the driving and inhibiting factors performance of the apparatus hospitals and health centers Tembalang subdistrict of Semarang City in applying Non-Smoking Area. The data obtained is used to formulate are commendation as a form of input in the sustain ability of application and implementation of Non-Smoking Area. The findings in the field showed that the implementation of Non-Smoking Areain Hospital and Health Center Tembalang subdistrict is already running in accordance with what is stated in Local Government Regulation No.3 year of 2013, where hospitals and health centers have been put on bansigns at NonSmoking Area. On the other side, there are still some short comings during the passage of this policy, where the lack of responsibility of from hospital and health center toward Local Government as policy maker. Execution of punishment in the form of imprisonment and fine can’t running yet. This indicates that the implementation process of Non-Smoking Area in hospital and health venter regional district Tembalang isn’t effective yet. There commendations can be given in order to improve the performance of Public Health Office of Semarang City as bearers of Non-Smoking Area policy as well as the hospital and health center district Tembalang as implementers of NonSmoking Area policy are to empower the related parties such as Public Health Office of Semarang City, hospitals and health centers to be more active, accelerate the establishment and ratification Supervision Team, in cooperation with Satpol PP, manage the budgets of Non-Smoking Area independently and transparently, Diponegoro National Hospital is expected to more active responding the new regulation.Key Words: Non-Smoking Area, Local Regulation, Evaluation, Performance